2014
DOI: 10.3109/08982104.2014.899366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lyophilization on liposomal encapsulation of salmon calcitonin

Abstract: Lyophilization resulted in an increase in encapsulation efficiency of sCT in PEGylated liposomes, even in the absence of a cryoprotectant, due to presence of micellar vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This effect was not observed for large liposomes due to the small quantity of non-entrapped drug in the original samples. Similar results have been found for salmon calcitonin liposomes [ 40 ]. The increases in Dh and PDI values observed in rehydrated liposomes from samples containing L, S, or T do not affect their suitability for pulmonary drug delivery.…”
Section: Discussionsupporting
confidence: 90%
“…This effect was not observed for large liposomes due to the small quantity of non-entrapped drug in the original samples. Similar results have been found for salmon calcitonin liposomes [ 40 ]. The increases in Dh and PDI values observed in rehydrated liposomes from samples containing L, S, or T do not affect their suitability for pulmonary drug delivery.…”
Section: Discussionsupporting
confidence: 90%
“…It was shown that dehydration–rehydration of the vesicles have numerous advantages such as comparatively better encapsulation efficiency and lower probable destabilization to the encapsulated drug. Moreover, freeze-drying is usually utilized as a means to increase the physical stability of BBVs. , Use of DEAE-Dx as a steric stabilizer for CBBVs caused an increase in particle size and increase in ZP due to the effect of cationic polymer DEAE-Dx . The slightly higher EE% of DEAE-Dx-stabilized BBVs may be due to the larger vesicle particle size compared to CBBVs .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, freeze-drying is usually utilized as a means to increase the physical stability of BBVs. 45,46 Use of DEAE-Dx as a steric stabilizer for CBBVs caused an increase in particle size and increase in ZP due to the effect of cationic polymer DEAE-Dx. 22 The slightly higher EE% of DEAE-Dxstabilized BBVs may be due to the larger vesicle particle size compared to CBBVs.…”
Section: ■ Discussionmentioning
confidence: 99%